Tunable Silver-Functionalized Porous Frameworks for Antibacterial Applications - Mark A. Isaacs; Brunella Barbero; Lee J. Durndell; Anthony C. Hilton; Luca Olivi; Christopher M. A. Parlett; Karen Wilson; Adam F. Lee (MDPI AG, 2018)
Healthcare-associated infections and the rise of drug-resistant bacteria pose significant challenges to existing antibiotic therapies. Silver nanocomposites are a promising solution to the current crisis, however their therapeutic application requires improved understanding of underpinning structure-function relationships. A family of chemically and structurally modified mesoporous SBA-15 silicas were synthesized as porous host matrices to tune the physicochemical properties of silver nanoparticles. Physicochemical characterization by transmission electron microscopy (TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), X-ray absorption near-edge spectroscopy (XANES) and porosimetry demonstrate that functionalization by a titania monolayer and the incorporation of macroporosity both increase silver nanoparticle dispersion throughout the silica matrix, thereby promoting Ag2CO3 formation and the release of ionic silver in simulated tissue fluid. The Ag2CO3 concentration within functionalized porous architectures is a strong predictor for antibacterial efficacy against a broad spectrum of pathogens, including C. difficile and methicillin-resistant Staphylococcus aureus (MRSA).